Plants mediate soil organic matter decomposition in response to sea level rise. (January 2016) - Mueller, Peter; Jensen, Kai; Megonigal, James Patrick
Abstract: Tidal marshes have a large capacity for producing and storing organic matter, making their role in the global carbon budget disproportionate to land area. Most of the organic matter stored in these systems is in soils where it contributes 2–5 times more to surface accretion than an equal mass of minerals. Soil organic matter (SOM) sequestration is the primary process by which tidal marshes become perched high in the tidal frame, decreasing their vulnerability to accelerated relative sea level rise (RSLR). Plant growth responses to RSLR are well understood and represented in century‐scale forecast models of soil surface elevation change. We understand far less about the response of SOM decomposition to accelerated RSLR. Here we quantified the effects of flooding depth and duration on SOM decomposition by exposing planted and unplanted field‐based mesocosms to experimentally manipulated relative sea level over two consecutive growing seasons. SOM decomposition was quantified as CO2 efflux, with plant‐ and SOM‐derived CO2 separated via δ 13 CO2 . Despite the dominant paradigm that decomposition rates are inversely related to flooding, SOM decomposition in the absence of plants was not sensitive to flooding depth and duration. The presence of plants had a dramatic effect on SOM decomposition, increasing SOM‐derived CO2 flux by up to 267% and 125% (in 2012 and 2013, respectively) compared to unplanted controls in the two growing seasons. Furthermore, plant stimulation of SOM decomposition was strongly and positively related to plant biomass and in particular aboveground biomass. We conclude that SOM decomposition rates are not directly driven by relative sea level and its effect on oxygen diffusion through soil, but indirectly by plant responses to relative sea level. If this result applies more generally to tidal wetlands, it has important implications for models of SOM accumulation and surface elevation change in response to accelerated RSLR.